Plasmid-Borne smr Gene Causes Resistance to Quaternary Ammonium Compounds in Bovine Staphylococcus aureus - Bjorland, Jostein (American Society for Microbiology, 2001)
Resistance to quaternary ammonium compounds (QAC) in staphylococci is common in hospital environments and has been described in the food industry. Little is known about staphylococcal QAC resistance associated with animal disease, although such disinfectants are widely used in veterinary medicine. In order to investigate the occurrence of QAC resistance in staphylococci isolated from QAC-exposed animals, 32 penicillin- and tetracycline-resistant and 23 penicillin- and tetracycline-susceptible Staphylococcus aureus isolates collected from milk from cows with mastitis during a 4-year period were selected for QAC susceptibility studies and genetic characterization. The isolates originated from four different herds that used a common pasture with a joint milking parlor in the summer. During the pasture season, a teat cream containing the QAC cetyltrimethylammonium bromide had been used daily for more than 10 years for mastitis control. Three of the penicillin- and tetracycline-resistant isolates, which were recovered from three different cows during a 20-month period, were resistant to QAC. Plasmid analysis, PCR, and DNA sequencing revealed a novel plasmid of 2,239 bp containing the smr gene. The plasmid, designated pNVH99, has similarities to small, smr-containing staphylococcal plasmids previously found in human and food isolates. pNVH99 is a new member of the pC194 family of rolling-circle replication plasmids. The three QAC-resistant isolates, as well as 28 of the 29 remaining penicillin- and tetracycline-resistant isolates, were indistinguishable by pulsed-field gel electrophoresis. The study indicates that the occurrence and spread of QAC-resistant S. aureus among dairy cows may be a problem that needs further investigation.